Cerebral venous sinus thrombosis in children: Clinical, imaging, laboratory findings and evaluation of relation to the platelet indices (Annals of Medical Research, 2021)
Aim: The aim of this study is to present clinical, imaging and laboratory findings of pediatric cerebral venous sinus thrombosis (CVST), and to evaluate any relationship between the platelet indices and CVST in children.Material and Methods: Clinical, laboratory and imaging findings of fifteen children with detected CVST on MRI examinations were recorded retrospectively. Fifteen controls were included in the study. All patients and controls were evaluated and platelet indices including; MPV, PDW, PC and MPV/plt ratio were compared.Results: There was no difference in age and gender distribution between patients and controls. The most common symptom in patients with CVST was headache and fever. Platelet count, PDW, MPV and MPV/plt ratio were slightly higher in controls, however there was no significant difference between two groups (p=0.2, p=0.486, p=0.47, p= 0.595, respectively). Prothrombotic state was found in 33% of our patients and all had increased homocysteine levels. The most common localization of thrombosis was transverse sinus with 50% involvement. Conclusion: This study presented clinical, MRI and laboratory findings of children with CVST and showed no difference in PC, MPV, PDW and MPV/plt ratio between patients and controls. Platelet indices may not be used to support the diagnosis of CVST in children.
Keywords: Sinus thrombosis; intracranial; child; mean platelet volume.